2003
DOI: 10.1097/01.prs.0000046249.33122.76
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Effect of Mastectomy with or without Breast Reconstruction: A Prospective, Multicenter Study

Abstract: A multicenter, prospective study ( = 103) examined the psychological implications of women's decisions for or against breast reconstruction. Recognized measures of anxiety, depression, body image, and quality of life were completed before the operation, and 6 and 12 months later. A reduction in psychological distress over the year following the operation was evident in each surgical group (mastectomy alone or immediate or delayed reconstruction), indicating that reconstructive surgery can offer psychological b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
195
2
13

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(222 citation statements)
references
References 30 publications
9
195
2
13
Order By: Relevance
“…The association with HT appears to be statistically significant, without any clear explanations. Nevertheless, CC remains difficult to assess, as illustrated by the high variance of data found in literature (17-68%) [12,18,[24][25][26]. This may be explained by differences in patient follow-up: rate of CCs increases with increasing duration of follow-up [30].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The association with HT appears to be statistically significant, without any clear explanations. Nevertheless, CC remains difficult to assess, as illustrated by the high variance of data found in literature (17-68%) [12,18,[24][25][26]. This may be explained by differences in patient follow-up: rate of CCs increases with increasing duration of follow-up [30].…”
Section: Discussionmentioning
confidence: 86%
“…IPMR using the TE/I technique after breast cancer offers cosmetic and psychological advantages [12] for both the patient and the surgeon, with only a few contraindications. Our study involved a sizeable and homogenous population of patients who underwent IPMR using the TE/I technique followed by RT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 19 articles (18.4%) mentioned the possible drawbacks of preventive mastectomy, e.g., the incidence of breast reconstruction prosthesis infection 34 or the emotional or psychological consequences that mastectomies have on women, even in cases when the operation is immediately followed by breast reconstruction. 35,36 When crosstabulated by country, the results showed discussions of these topics in six articles published in Canada, six articles in the United States, and seven in the United Kingdom. Nonetheless, 33 articles (32%) did mention the benefits of evidence-based decisions regarding BRCA1/2 testing and genetic risk assessment.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the baseline assessment in this sample appears to indicate only moderate impairment of cognitive functioning. Finally, the lack of change with regard to body image needs to be considered in comparison with studies that have demonstrated an improvement in body image over time, especially in women who have undergone mastectomy [41]-probably due to increasing skills in coping with body image impairment. The controversial finding of a lack of change in body image might be explained by the high percentage of women in the present study who were treated with BCT (92%); the scores for body image in the sample were consequently fairly high over all measurement time-points and are thus not comparable with data from studies in which the majority of patients were treated with mastectomy [20].…”
Section: Change Of Qolmentioning
confidence: 99%